Caregivers’ Malaria Knowledge, Beliefs and Attitudes, and Related Factors in the Bata District, Equatorial Guinea - Romay-Barja, Maria (PLoS One, 2016)
OBJECTIVES: Adequate community knowledge about malaria is crucial in order to improve prevention by reducing exposure to the disease. Malaria is a major cause of morbidity and mortality among children of less than five years of age in Equatorial Guinea. However, information concerning the accuracy of community knowledge is insufficient. This study aimed at assessing the depth of caregivers’ knowledge of malaria, their beliefs and attitudes about this disease, and their socioeconomic determinants in the Bata district of Equatorial Guinea. METHODOLOGY: A cross-sectional study was conducted in the district of Bata, involving 440 houses selected from 18 rural villages and 26 urban neighbourhoods. A combined "Malaria Knowledge Score" was generated based on caregivers’ knowledge about transmission, symptoms, prevention, the treatment of children, and best place to seek treatment. Multivariate logistic regressions analyses were performed to assess those factors that are associated with knowledge about malaria. RESULTS: A total of 428 caregivers were interviewed; 255 (59.6%) and 173 (40.4%) lived in urban and rural areas respectively. Significant differences between rural and urban households were observed in caregivers’ malaria knowledges and beliefs. Almost 42% of urban and 65% of rural caregivers were unaware as to how malaria is transmitted (OR = 2.69; 95% CI: 1.78–4.05). Together with rurality, the factors most significantly associated with the Malaria Knowledge were the level of education of the caregiver and the socioeconomic status of the household. CONCLUSIONS: Improvements in educational programs are needed to empower the most vulnerable households such that they can pro-actively implement malaria control measures. This could be achieved by a comprehensive communication strategy aimed at changing individual and community behaviours, and delivered by suitably trained community health workers and indoor residual spraying personnel.